Perception and attitude of Korean physicians towards generic drugs - Mikyung Ryu; Juyoung Kim (BMC, 2017)
Abstract Background In 2012, a new pharmaceutical policy was introduced in Korea. According to the new policy, off-patent brand-name drugs (original drugs) and generic drugs must be priced the same. Methods This study aims to investigate the perception and attitude of Korean physicians towards generic drugs before and after the policy reform. Surveys were conducted with registered doctors at the Health Insurance Review Agency (HIRA) twice, in 2011 and 2013, by means of email and HIRA online survey systems. Results In the 2011 survey, 82% knew about the bioequivalent (BE) guideline, whereas only 25.7% trusted BE testing results. More than half preferred original drugs to generic drugs because of clinical experience and generic drugs confidence limits. 64.2% pointed out that the Korean generic drugs prices are more expensive than in other counties. In the 2013 survey, 73% preferred original drugs to generic drugs because of believed difference in drug effectiveness. After the pricing policy reform, 35.5% stated that they didn't change their prescribing pattern, whereas 29.7% stated that they began prescribing generic drugs. Conclusions The Korean government has revised and strengthen the guideline on BE test to improve the quality and confidence of generic drugs. Although generic drugs prescription was increased slightly more than the 2011 survey, 2013 survey showed that around 70% of respondents still preferred original drugs.